Clozapine re-challenge and initiation following neutropenia: a review and case series of 14 patients in a high-secure forensic hospital. (June 2021) - Silva, Edward; Higgins, Melanie; Hammer, Barbara; Stephenson, Paul
Objective: Clozapine remains the most effective intervention for treatment resistant schizophrenia; however, its use is prohibited following neutropenias. We review neutrophil biology as applied to clozapine and describe the strategies to initiate clozapine following neutropenia used in a case series of 14 consecutive patients rechallenged in a United Kingdom (UK) high-secure psychiatric hospital. We examine outcomes including the use of seclusion and transfer. Methods: A case series of 14 male patients with treatment resistant schizophrenia treated with clozapine despite previous episodes of neutropenia between 2006 and 2015 is presented. Data were collected during 2015 and 2019. Using this routinely collected clinical data, we describe the patient characteristics, causes of neutropenia, the strategies used for rechallenging with clozapine and clinical outcomes. Results: Previous neutropenias were the result of benign ethnic neutropenia, clozapine, other medications and autoimmune-related. Our risk mitigation strategies included: granulocyte-colony stimulating factor (G-CSF), lithium and watch-and-wait. There were no serious adverse events; at follow up half of the patient's had improved sufficiently to transfer them to conditions of lesser security. There were dramatic reductions in the use of seclusion. Conclusion: Even in this extreme group, clozapine can be safely and effectively re/initiated following neutropenias, resulting in marked benefits for patients. This requires careful planning based on an understanding of neutrophil biology and the aetiology of the specific episode of neutropenia.